Pathways of social goals, academic emotions, and self-regulated learning of Filipino learners - Ibalobor, Ma. Roxanne B. (Animo Repository, 2019)
Pekrun’s (2006) Control-Value Theory was used as a theoretical framework in this study in order to provide evidence on the mediating role of academic emotions between the relationship of social goals and self-regulated learning among 801 Filipino learners in the public and private tertiary educational institutions. It employed a pragmatic research philosophy and utilized mixed methods research particularly sequential explanatory design. Results of the quantitative phase showed that 14 of the 16 pathways are significant, thus confirmed the following hypotheses: (1) Anxiety, hope and enjoyment mediate the relationship of social affiliation goals with self-regulated learning among Filipino learners; (2) Anxiety mediates the relationship of social responsibility goals with self-regulated learning among Filipino learners; and (3) Enjoyment mediates the relationship of social concern goals with self-regulated learning among Filipino learners. The significant pathways include the significant direct effects of social concern goals on cognitive and motivational regulation, social affiliation goals on motivational regulation, and social responsibility goals on cognitive regulation. Phase 2 highlighted 6 cases with specific stories of student experiences that embed the quantitative results of this study in order to further expound the mediating effects of achievement emotions as experienced by individual students. Social goals activated achievement emotions, which in effect activated both cognitive and motivational self-regulation (Boekaerts, 1996). Discussion of the findings integrating the quantitative and qualitative results, recommendation, and future research direction are also included in this paper.